The Paradigm Shift in Law Enforcement in State-Owned Enterprises: An Analysis of the Restrictions on the Role of KPK - Pujiwati Wiantin; Gautama Budi Arundhati; Al Khanif (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2025)
This study is motivated by the dual role of State-Owned Enterprises (BUMN) as business actors and agents of national development, which makes them vulnerable to governance issues, including corruption and abuse of authority. The supervision by the Corruption Eradication Commission (KPK), which has been crucial, becomes limited after the removal of the status of state administrators for SOE officials based on Law No. 1 of 2025. This creates new challenges in maintaining SOE accountability, thus requiring strengthening of supervisory mechanisms through civil law and the application of Good Corporate Governance principles. This study uses a normative legal approach with doctrinal legal research, focusing on normative-conceptual analysis of the paradigm shift in law enforcement in State-Owned Enterprises (BUMN), particularly the limitation of the Corruption Eradication Commission’s (KPK) authority from a civil law perspective. The research method combines three approaches: the statutory approach to review relevant regulations, the conceptual approach to explore applicable legal principles and theories, and the case approach to analyze court decisions related to law enforcement against SOE officials.